The sleeping beauty - Čajkovskij, Pëtr Ilʹič 1840-1893 (C Major Entertainment GmbH, 2020)
Indeed, it was to La Scala in 1966 that Rudolf Nureyev entrusted the debut of 'his' Sleeping Beauty, and now, twelve years after its last performance, his masterpiece returns to the stage with the magnificent sets created by Oscar winner Franca Squarciapino at La Scala in 1993, and Felix Korobov conducting the extraordinary score by Tchaikovsky. Florence Clerc is in charge of the choreographic revival, and the result is nothing short of extraordinary
Interpreten unter anderem: Polina Semionova (Princess Aurora), Timofej Andrijashenko (Désiré), Alessandro Grillo (King Florestan XXIV), Marta Romagna (the Queen) ; Ballet Company of Teatro Alla Scala ; Orchestra of Teatro Alla Scala ; Felix Korobov, conductor
Live-Aufnahme: Mailand, Teeatro alla Scala, 2019
Bildformat: 16:9
Keywords: Ballets; Filmed ballets; Filmed performances; Film; Blu-Ray-Disc